1974
DOI: 10.1139/v74-600
|View full text |Cite
|
Sign up to set email alerts
|

Thermolysis of Some 4-Alkylidene-1-pyrazolines

Abstract: . Can. J. Chem. (1974).The thermolysis of 4-methylene-1-pyrazoline and the kinetic isotope effects of 3,3-d,, 3,3,6,6-d4, and 3,3,5,5,6,6-d6 compoilnds were examined. Data suggest a simultaneous cleavage of both carbon-nitrogen bonds with the formation of an intermediate which by 13C labelling is shown to be other than the triplet planar trimethylenemethane. Product studies on 3,3-dimethyl-4-methylene-1-pyrazoline and 4-isoplopylidene-1-pyrazoline are best rationalized in terms of the Chesick type intermediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0

Year Published

1975
1975
1981
1981

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Indeed Dowd et al (8) have demonstrated that the triplet is the ground state for 7 and that it can be generated photochemically from 4. While our first efforts to define the mechanism of thermolysis of 4 suggested that, on the basis of secondary deuterium kinetic isotope effects, both C-N bonds are cleaving in the rate determining step, our later work with methylated derivatives suggests that the system is very sensitive to steric factors, and that the mechanism changes on going from 4 to 3,3,5,5-tetramethyl-4-methylene-1-pyrazoline (9); the activation energy increases from 32 kcal mol-' for 4 (10) to 40 kcal mol-' for 9 (1 1). Consequently we have undertaken a detailed study of the secondary deuterium isotope effects on 10-14, both of the kinetics and of the product distributions.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…Indeed Dowd et al (8) have demonstrated that the triplet is the ground state for 7 and that it can be generated photochemically from 4. While our first efforts to define the mechanism of thermolysis of 4 suggested that, on the basis of secondary deuterium kinetic isotope effects, both C-N bonds are cleaving in the rate determining step, our later work with methylated derivatives suggests that the system is very sensitive to steric factors, and that the mechanism changes on going from 4 to 3,3,5,5-tetramethyl-4-methylene-1-pyrazoline (9); the activation energy increases from 32 kcal mol-' for 4 (10) to 40 kcal mol-' for 9 (1 1). Consequently we have undertaken a detailed study of the secondary deuterium isotope effects on 10-14, both of the kinetics and of the product distributions.…”
Section: Introductionmentioning
confidence: 93%
“…The deuterated 4-methylene-1-pyrazolines, 10, 11, and 12 were prepared by methods described earlier (10) and their deuterium content assessed by (a) low ionization potential mass spectrometry, (b) 'Hmr, and (c) 'Hmr. The tetradeuterio compound 13 was prepared by the methods outlined in Scheme 1.…”
Section: Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Structurally modified 4-inethylene-I-pyrazolines such as the bicyclic system (38) studied by Berson and collaborators (2) have been demonstrated to produce both singlet and triplet 1,3-diyls, by both photolysis and thermolysis, as evidenced by trapping experiments and by dimer formation. The kinetics of thermolysis of 4-methylene-1-pyrazoline (I) and its deuterium-and '3C-labelled derivatives have implicated a nitrogen free diyl as a possible intermediate (3). Theoretical studies (4) have suggested that for singlet triinethylenen~ethane the orthogonal diyls are more probable than is the planar species.…”
mentioning
confidence: 99%
“…We have shown that the product proportions from the thermolysis of 4-isopropylidene-1-pyrazoline (7)' and 3,3-dimethyl-4-methylene-1-pyrazoline (6) are easily' rationalized in terms of the intermediates 39a and 39b in Scheme 1. These intermediates were postulated on the basis of the least motion principle and the presumed cleavage o f both carbon nitrogen bonds as implicated from the kinetic studies o n 1 (3). The product proportions from deuterium labelled 1 cannot be.reconciled with a inechanisin analogous to Schei~le 1.…”
mentioning
confidence: 99%